Modeling of the effect of the void shape on effective ultimate tensile strength of porous materials: Numerical homogenization versus experimental results. (September 2017) - Masmoudi, M.; Kaddouri, W.; Kanit, T.; Madani, S.; Ramtani, S.; Imad, A.
Highlights: Numerical homogenization used to compute mechanical properties of porous materials. Several configurations obtained by varying the voids morphology and porosity. The representative volume element is used in order to estimate the morphology effect. Confrontation of the obtained numerical results to an analytical and experimental data. A formula improving the Boccaccini model is proposed. Abstract: A numerical homogenization technique and morphological analysis based on the finite element method are used to compute mechanical properties of porous materials. This is achieved by considering two–dimensional matrix containing random distribution of identical non–overlapping circular or elliptical voids. Several microstructure configurations are obtained by varying the voids morphology and the porosity of the matrix. The notion of the representative volume element is used for numerical simulations in order to estimate the morphology effects of the voids on the effective ultimate tensile strength of the called Lotus – Type Porous Metals . A confrontation of the obtained numerical results of the representative microstructures for different morphologies of voids and different porosities to an analytical model and experimental data is performed. Finally, a formula improving the Boccaccini model is proposed to estimate effective tensile strength of porous metals taking into account the voids morphology.